International Air Travel to Ohio, USA, and the Impact on Malaria, Influenza, and Hepatitis A - Donald E. Brannen; Ali Alhammad; Melissa Branum; Amy Schmitt (Scientifica)
The State of Ohio led the United States in measles in 2014, ostensibly related to international air travel (IAT), and ranked lower than 43 other states in infectious disease outbreak preparedness. We conducted a retrospective cohort study using surveillance data of the total Ohio population of 11 million from 2010 through 2014 with a nested case control of air travelers to determine the risk of malaria, seasonal influenza hospitalizations (IH), and hepatitis A (HA) disease related to international travel and to estimate the association with domestic enplanement. IAT appeared protective for HA and IH with a risk of 0.031 (.02–.04) but for malaria was 2.7 (2.07–3.62). Enplanement increased the risk for nonendemic M 3.5 (2.5–4.9) and for HA and IH 1.39 (1.34–1.44). IAT’s ratio of relative risk (RRR) of malaria to HA and IH was 87.1 (55.8–136) greater than 219 times versus domestic enplanement which was protective for malaria at 0.397 (0.282–0.559). Malaria is correlated with IAT with cases increasing by 6.9 for every 10,000 passports issued.